Current and Voltage Monitoring in Wind Power Plants Using ESP8266 and Node-Red - Rozihan Arief; Mohamad Irfan Faudi Maulana (Universitas Negeri Surabaya or The State University of Surabaya, 2024)
Fossil energy which is the main energy producer can be converted by utilizing wind power as an alternative renewable energy. The tool used as a wind power converter is a wind turbine, where wind power is kinetic energy that is converted into mechanical energy which is used to produce alternative energy is electrical energy. The working principle of this generator comes from the kinetic energy of the wind that rotates the propeller or windmill, then this mechanical energy runs the generator to create electrical energy. The design is carried out to find out and understand about operating Wind Power Plant Monitoring using Node-Red-based ESP8266 which is integrated with a smartphone or PC as a monitor for the tool. The design of the Wind Power Plant voltage and current monitor uses the ESP8266 microcontroller and the programmer uses the Arduino IDE software which will be applied to Node Red to create a display on the smartphone or PC screen. This study aims to produce a wind turbine prototype using the Savonius wind turbine model and monitor the output of the wind power plant using the ESP8266 which is displayed using the Node-Red dashboard.